PECULIARITIES OF GIG-CONTRACTS STATED BY RESIDENTS OF THE LEGAL REGIME DIIA CITY - Tarasiuk, Serhii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to study the peculiarities of the use of gig contracts as a separate type of civil law contracts in the context of the Law of Ukraine «On Stimulating the Development of the Digital Economy in Ukraine». Conduct a comparative analysis of the effectiveness of the settlement of relations for the provision of services (performance of works) in favor of residents of legal regime Diia City specialists in the field of information technology in comparison with employment contracts. To draw conclusions about the prospects for the application of gig contracts in the legal regime of Diia City and the possibility of applying it outside. Methods of research: general and special legal methods, including analysis, system functional method and formal juridical method. Results: the basic conditions for concluding a gig contract by residents of Diia City are summarized and the prospects of this type of civil law relations in the digital economy are proved. Discussion: the constant increase in the importance of the digital economy in the global economy encourages to improve the legal regulation of the IT industry, which aims to create attractive conditions for the operation of this type of business in Ukraine. The Law of Ukraine «On Stimulating the Development of the Digital Economy in Ukraine» introduces the gig contract as a kind of service agreement (performance of works) aimed at regulating a new type of relationship between digital economy entities in the form of residents of the action regime Diia City and gig specialists. The introduction of the gig contract is a novelty in civil law and a special subtype of the service contract and the contract. A prerequisite for the right to enter into a gig contract is the subjective composition of the parties to such agreements, which in turn limits its widespread application. On the other hand, the purpose of this agreement is to preserve the balance of rights and obligations of the parties inherent in labor law, which usually arouses scientific interest and the need for research, which are currently a key factor in Ukraine's competition for the first lines in the world's digital GDP. In order to study other opinions about the application and features of gig contracts, research has been conducted by other scientists and lawyers. The article examines the advantages and disadvantages of gig contracts compared to employment contracts and the possibility of using gig contracts outside the legal regime of Diia City.